Temperature-induced formation of Pd nanoparticles in heterogeneous nanobiohybrids - Losada-Garcia, Noelia (2023)
This work was supported by the Spanish Government, the Spanish National Research Council (CSIC). We also thank Dr Martinez from Novozymes. Publisher Copyright: © 2023 RSC.